Oxytocin Dynamics in the Body and Brain Regulated by the Receptor for Advanced Glycation End-Products, CD38, CD157, and Nicotinamide Riboside - Higashida, Haruhiro; Furuhara, Kazumi; Lopatina, Olga; Gerasimenko, Maria; Hori, Osamu; Hattori, Tsuyoshi; Hayashi, Yasuhiko; Cherepanov, Stanislav M.; Shabalova, Anna A.; Salmina, Alla B.; Minami, Kana; Yuhi, Teruko; et al. (Frontiers in Neuroscience, 2022)
Investigating the neurocircuit and synaptic sites of action of oxytocin (OT) in the brain is critical to the role of OT in social memory. To the same degree, it is important to understand how OT is transported to the brain from the peripheral circulation. To date, of these, many studies provide evidence that CD38, CD157, and receptor for advanced glycation end-products (RAGE) act as regulators of OT concentrations in the brain and blood. It has been shown that RAGE facilitates the uptake of OT in mother’s milk from the digestive tract to the cell surface of intestinal epithelial cells to the body fluid and subsequently into circulation. RAGE has been shown to recruit circulatory OT into the brain from blood at the endothelial cell surface of neurovascular units. Therefore, it can be said that extracellular OT concentrations in the brain (hypothalamus) could be determined by the transport of OT by RAGE from the circulation and release of OT from oxytocinergic neurons by CD38 and CD157. In addition, it has recently been found that gavage application of a precursor of nicotinamide adenine dinucleotide (NAD), nicotinamide riboside, for 12 days can increase brain OT in mice. Here, we review the evaluation of the new concept that RAGE is involved in the regulation of OT dynamics at the interface between the brain, blood, and intestine in the living body, mainly by summarizing our recent results due to the limited number of publications on related topics. And we also review other possible routes of OT recruitment to the brain.